Safarboy Rozimboyev is an active researcher of Khorezm folklore - Maxsuda Yusupboyevna Karimova (Zien Journals, 2022)
The article discusses the study of Uzbek folklore in the 20th century, in particular, the study ofthe epics of Khorezm, the publication of the epics of the Khorezm series "Ashiqnoma". effective research onUzbek epics by professor Safarboy Rozimboyev, a folklorist scientist, is analyzed. It is stated that folkloresamples should be preserved as unique intangible cultural heritage
Keywords: The scientist's first folklore expedition,